PENGARUH METODE OUTING CLASS TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV SDN GUGUS NAKULA KABUPATEN PEMALANG PADA MATA PELAJARAN IPAS - Maghfiroh; Petra Kristi Mulyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The low learning outcomes of students can be influenced by the lack of innovation of educators in choosing learning methods used in the learning process. This study aims to determine the effect of the outing class method on the learning outcomes of fourth grade students of SDN Gugus Nakula Pemalang Bone. This study uses quantitative experimental method with quasi-experimental design with nonequivalent control group design. The sampling used in this study is non probability sampling. Data collection techniques through interviews, tests and documentation. The results of hypothesis testing obtained value t count (2.850) > t table (2.006). Thus, it can be stated that t count is greater than t table (2,850 > 2.006). Based on this, it can be concluded that there is an influence of outing class method on the learning outcomes of fourth grade students of SDN Gugus Nakula Pemalang Bone on IPAS subjects.